Awareness and Acceptance of Family Planning in Patients Coming to Gynae Department of D.G.Khan Teaching Hospital (Medical Forum Monthly, 2024)
Objective: To determine the frequency of awareness and acceptance of contraception in married women.Study Design: Cross sectional descriptive study. Place and Duration of Study: This study was conducted in department of Obs and Gynae of D.G.Khan teaching hospital from 1st April 2014 to 1st April 2015.Materials and Methods: A questionnaire was designed and it was filled by interview of 200 women. This questionnaire carried socio demographic characteristics of women as well as knowledge and acceptance. This questionnaire includes knowledge of name of different methods and how to access these methods.Results: As the result, 92.5% women were aware on one family planning method out of 10 but acceptance for usage in one only 60% .The contraceptive prevalence was 33% which was less than 35% CPR from Pakistan national prevalence. Depo-Provera method is followed quit 70% as compared to oral contraceptive pills 68% and natural method 50% least known method was vaginal foam tablets/ Jelly 20%. Regarding permanent method, knowledge of sterilization awareness was 81% in females and 60% was in males. Emergency contraception awareness was low 11.5% as in table two.Conclusion: More efforts are required with the collaboration of print and electronic media to educate the public about the safety and convenience of modern irreversible as well as reversible methods of family planning.